Pengenalan Story Telling Sebagai Media untuk Meningkatkan Pembelajaran Bahasa Inggris di SMP Negeri 1 Aluh-aluh - Yuliani, Novi Dwi; Azmy, Fikri Fuadi; Isnaniah, Isnaniah; Noor, Pajrian (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to introduce the story telling to the teachers and students at SMP Negeri 1 Aluh-aluh as a teaching media to improve English learning. Story telling is a good and complex teaching media for teaching skills in English. Among the benefits of using story telling include: sharpening writing, reading, speaking and listening skills in English, enriching vocabulary, phrases and knowledge of English idioms and proverbs, practicing public speaking skills as well as pronunciation, increasing self-confidence in English and studying various aspects of life contained in stories. The implementation of this community service activity uses the socialization method on how to use story telling in learning, direct teaching practice using story telling, and giving prizes as a form of motivation for students who are able to demonstrate story telling. The conclusion from this service activity is that this service activity ran smoothly and had a positive impact on teachers and students at SMP Negeri 1 Aluh-aluh. Teachers and students can start practicing using story telling media after this community service is carried out.